Timing of headache after COVID-19 vaccines and its association with cerebrovascular events: An analysis of 41, 700 VAERS reports. (October 2022) - Garcia-Azorin, David; Baykan, Betül; Beghi, Ettore; Doheim, Mohamed F; Fernandez-de-las-Penas, Cesar; Gezegen, Hasim; Guekht, Alla; Hoo, Fan Kee; Santacatterina, Michele; Sejvar, James; Tamborska, Arina A; Thakur, Kiran T; et al.
Abstract: Background: Delayed-onset of headache seems a specific feature of cerebrovascular events after COVID-19 vaccines. Methods: All consecutive events reported to the United States Vaccine Adverse Reporting System following COVID-19 vaccines (1 January to 24 June 2021), were assessed. The timing of headache onset post-vaccination in subjects with and without concomitant cerebrovascular events, including cerebral venous thrombosis, ischemic stroke, and intracranial haemorrhage was analysed. The diagnostic accuracy in predicting concurrent cerebrovascular events of the guideline- proposed threshold of three-days from vaccination to headache onset was evaluated. Results: There were 314, 610 events following 306, 907, 697 COVID-19 vaccine doses, including 41, 700 headaches, and 178/41, 700 (0.4%) cerebrovascular events. The median time between the vaccination and the headache onset was shorter in isolated headache (1 day vs. 4 (in cerebral venous thrombosis), 3 (in ischemic stroke), or 10 (in intracranial hemorrhage) days, all P < 0.001). Delayed onset of headache had an area under the curve of 0.83 (95% CI: 0.75–0.97) for cerebral venous thrombosis, 0.70 (95% CI: 0.63–76) for ischemic stroke and 0.76 (95% CI: 0.67–84) for intracranial hemorrhage, and >99% negative predictive value. Conclusion: Headache following COVID-19 vaccination occurs within 1 day and is rarely associated with cerebrovascular events. Delayed onset of headache 3 days post-vaccination was an accurate diagnostic biomarker for the occurrence of a concomitant cerebrovascular events.